Manajemen Dalam Penanganan Konflik Dalam Lembaga Pendidikan - Surya Pratama, Muhammad Adi; Setiawan, Farid; Andriana, Ellyka; Maziya, Tsalisa (Universitas Darunnajah Jakarta, Indonesia, 2022)
Conflict management is a process of parties involved in conflict or parties who can devise conflict strategies and use them to control conflicts to generate a way out of the desired problem. Conflict is one of the foundations of human life and development that has different characteristics and attitudes. Conflict will always occur in the world as it happens in a social that can be called a state, nation, organization, company, school, even often occurs also in the smallest social consisting of a family, friendships and conflicts in yourself, surely a conflict will occur. The method used in compiling this research is a method of literature studies. The study of literature is taken from several sources such as scientific articles, the internet, and also documentation books. The material studied comes from national and international journal books and articles relevant to the theme of the discussion, namely Conflict Management in Educational Institutions. Conflict comes from the word confligere, conflictuan which means clashing with each other. All clashing, collisions, different, opposition, fights. Conflict is the opposition to a person's desires that is different from what is desired, whether between individuals, groups or organizations. In the discussion discussing knowledge of conflict, types of conflicts, causes, sources, impacts will help leaders in finding ways to form conflict management strategies appropriately and correctly.